2013
DOI: 10.1371/journal.pone.0052186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aripiprazole on Mismatch Negativity (MMN) in Schizophrenia

Abstract: BackgroundCognitive deficits are considered core symptoms of the schizophrenia. Cognitive function has been found to be a better predictor of functional outcome than symptom levels. Changed mismatch negativity (MMN) reflects abnormalities of early auditory processing in schizophrenia. Up to now, no studies for the effects of aripiprazole on MMN in schizophrenia have been reported.Methodology/Principal FindingsSubjects included 26 patients with schizophrenia, and 26 controls. Psychopathology was rated in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
0
30
1
Order By: Relevance
“…There is considerable 1 The reduction in MMN amplitude is assumed to be independent of psychotic state based on observations that it rarely correlates with symptoms and remains smaller than MMN in controls even when clinical symptoms improve (for review, see Umbricht and Krjles, 2000). Of note a recent study by Zhou et al (2013) found that Aripiprazole increased MMN size and reduced psychosis symptoms, however post treatment MMN remained significantly smaller than that in healthy controls. evidence that this change in responsiveness is more than just passive neural adaptation (Friston, 2005;Kiebel et al, 2008;Näätänen et al, 2005;Winkler, 2007).…”
Section: The Prediction Error Account and Schizophreniamentioning
confidence: 86%
See 3 more Smart Citations
“…There is considerable 1 The reduction in MMN amplitude is assumed to be independent of psychotic state based on observations that it rarely correlates with symptoms and remains smaller than MMN in controls even when clinical symptoms improve (for review, see Umbricht and Krjles, 2000). Of note a recent study by Zhou et al (2013) found that Aripiprazole increased MMN size and reduced psychosis symptoms, however post treatment MMN remained significantly smaller than that in healthy controls. evidence that this change in responsiveness is more than just passive neural adaptation (Friston, 2005;Kiebel et al, 2008;Näätänen et al, 2005;Winkler, 2007).…”
Section: The Prediction Error Account and Schizophreniamentioning
confidence: 86%
“…(Cornblatt et al, 1989;Cornblatt and Keilp, 1994;Fisher et al, 1994;Nuechterlein et al, 1994), not remediated by psychotropic medication (Catts et al, 1995;Nielsen et al, 2012;Schall et al, 1998;Shinozaki et al, 2002;Umbricht et al, 1998;Umbricht et al, 1999;cf. Lavoie et al, 2008;Zhou et al, 2013), and has been observed in clinical high-risk individuals (Bodatsch et al, 2011;Nuechterlein, 1983;Pflueger et al, 2007) and equivocally in asymptomatic first-degree relatives (Cornblatt and Keilp, 1994;Bramon et al, 2004;Jessen et al, 2001;Magno et al, 2008;Michie et al, 2002;Nuechterlein et al, 1994;Rosburg et al, 2004). Although both reduced MMN and attentional impairments are heavily studied in schizophrenia, they are typically studied independently of each other.…”
Section: Mmn and Attention In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the cognitive deficits of schizophrenia, there are not many studies demonstrating that MMN reductions are well-treatedby current antipsychotic drugs [see (Todd et al, 2013;Umbricht and Krljes, 2005) for review, (Zhou et al, 2013) for a positive study], and therefore also reflect the features of the disorder that remain resistant to treatment. In addition, as a neurophysiological feature rather that a behavioural one, the MMN provides a unique opportunity for translation into rodent models.…”
Section: The Need For Animal Modelsmentioning
confidence: 99%